(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
This work compares the project costs of two possible decommissioning strategies for a hypothetical nuclear site with similar characteristics to the CNAAA reactors. The cost of the process is sensitive to the type of strategy adopted, as the type of strategy involves the duration of the process. Defining project strategy/duration and estimating cost are part of a coupled problem. Thus, decommissioning cost is a relevant step and needs to be rigorously defined before starting the decommissioning process, as demobilizing teams/equipment, and remobilizing entail extra costs. Cost estimates follow the Av-Descom model. Tool easily implemented by a spreadsheet-like code. Among the stages of the two strategies presented, the one with the greatest impact on the cost of the project is the stage referring to the transition period comprised by the decontamination tasks of the systems, equipment, and structure of the deactivated NPP. This step exposes workers to radiation doses and to the greatest occupational hazards. It was observed that the cost variation from one strategy to another is above 50% of the total cost of the project. It was concluded that defining the best decommissioning strategy is complex and important to be defined from the beginning of the decommissioning process. It was inferred that the strategy that best fits the Brazilian reality is the delayed decommissioning.